2016
DOI: 10.1513/annalsats.201512-798oc
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Social Determinants of Health Associated with Intensive Care Admission for Asthma in Children

Abstract: Social and economic risk factors typically predictive of increased asthma morbidity, including exposure to tobacco smoke, were not associated with ICU admission among a population of children admitted to the hospital for treatment of acute asthma. Intrinsic disease factors, including allergic sensitization, may be more important predictors of ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
(57 reference statements)
3
28
1
Order By: Relevance
“…Epstein et al found that lower income, Latino race, and children with government insurance were all associated with higher disease severity at the time of admission to the ICU . Some studies have focused on the impact of social determinants on asthma ICU admissions, but with conflicting results . Moghaddas et al found asthmatic patients admitted to the ICU had a lower socioeconomic index when compared to those admitted to the general ward .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epstein et al found that lower income, Latino race, and children with government insurance were all associated with higher disease severity at the time of admission to the ICU . Some studies have focused on the impact of social determinants on asthma ICU admissions, but with conflicting results . Moghaddas et al found asthmatic patients admitted to the ICU had a lower socioeconomic index when compared to those admitted to the general ward .…”
Section: Discussionmentioning
confidence: 99%
“…Moghaddas et al found asthmatic patients admitted to the ICU had a lower socioeconomic index when compared to those admitted to the general ward . McDowell et al, on the other hand, found intrinsic disease factors, such as allergic sensitization, were more important for ICU admission among asthmatic patients . Other studies have investigated the impact of social determinants on ICU procedures and outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28, 29 Although a pooled analysis of birth cohorts found that pet ownership did not modify the risk of asthma onset in children, 30 sensitized children who own pets may be at higher risk for severe asthma exacerbation requiring intensive care. 31 Cat and dog ownership also contributes to higher indoor endotoxin concentrations, which have been associated with wheezing and increased respiratory medication use. 32 Indoor dust mite and mold exposures are other risk factors that have also been linked to exacerbations of asthma in children.…”
Section: Discussionmentioning
confidence: 99%